Controllability of Neutral Fractional Functional Differential Equations with Two Caputo Fractional Derivatives (Journal of Nonlinear Modeling and Analysis, 2024)
Multiple fractional derivatives enrich the dynamic properties offractional differential equations. This paper concerns with neutral fractionalfunctional differential equations with two Caputo fractional derivatives. Byusing the fixed point methods with the fractional integral inequalities, theexistence results and controllability of the equations are considered in thecases of finite delay and infinite delay, respectively. An example is given toillustrate the main results.